Pharmacokinetically-based prediction of the effects of antibiotic combinations on resistant Staphylococcus aureus mutants: in vitro model studies with linezolid and rifampicin. (4th July 2017) - Firsov, Alexander A.; Golikova, Maria V.; Strukova, Elena N.; Portnoy, Yury A.; Dovzhenko, Svetlana A.; Kobrin, Mikhail B.; Zinner, Stephen H.
Abstract : To explore if combinations of linezolid (L) with rifampicin (R) are able to restrict Staphylococcus aureus resistance, the enrichment of L- and R-resistant mutants was studied in an in vitro dynamic model. L- and R-resistant mutants were enriched in all single drug treatments. In contrast, L-resistant mutants were not enriched and R-resistant mutants were similar to baseline amounts with only minimal regrowth at the end of the combination treatments. These effects appear to be explained by lowering the mutant prevention concentration (MPC) for L+R combinations (MPCL+R ) compared to the MPCs of L and R alone (MPCL and MPCR ) and thereby the longer times above MPCL+R (73–100% of the dosing interval for L and 42–58% for R) compared to the times above MPCL (0–44%) and MPCR (0%). These findings provide an opportunity to predict the selection of S. aureus resistance in L+R treatments using MPCL+R s.